Experimental Photography Study by Kurnia Ngayuga Wibowo “Memory Lane” - Abdul Aziz Al Hakim; Raden Bima Sakti Arnanda A; Rizky Dwi Andini; Khaerudin Imawan; Dedet Erawati (International Journal Labs, 2024)
The work Experimental Photo Memory Lane by Kurnia Ngayuga Wibowo is a notable piece that has been featured in various prestigious exhibitions, such as